Isozyme segregation in five apple progenies and potential use for map construction - Chevreau, Elisabeth; Gallet, Michel; Manganaris, George A. (My University, 1999)
In the framework of the European Apple Genome Mapping Project, five apple progenies were scored for 53 isozyme markers and two phenotypic monogenic characters, R t (anthocyanin production in all tissues) and C o (columnar habit). The collaboration between two teams (in France and Greece) enabled a clarification of the synonymy between existing isozyme loci designations and the description of 12 new loci. The two phenotypic loci and the majority of the isozyme loci segregated in accordance with the expected monogenic ratios. Twenty percent of the scored segregations involved markers segregating for both parents, but only 9% involved more than two alleles. Thus, only a few isozyme markers (Aat-1, Fdh-1, Pgd-1, Pgm-1, Prx-3, Prx-C1 and Sod-4) were particularly informative for mapping purposes. Joint segregation analysis located 36 isozyme markers together with the two phenotypic loci, R t and C o , in 11 linkage groups, most of which could be related to already published maps. Thus, despite their limited number, polymorphic apple isozyme markers are valuable as anchor points to establish a reliable correspondence between genetic maps built from separate progenies.
Keywords: Apple; Isozymes; Compact habit; Linkage; Genome mapping